Attraction loyalty, destination loyalty, and motivation: agritourist perspective. Issue 9 (3rd May 2021) - Leo, Gundur; Brien, Anthony; Astor, Yackob; Najib, Mukhamad; Novianti, Syifaa; Rafdinal, Wahyu; Suhartanto, Dwi
ABSTRACT: This study evaluates the link between tourists' loyalty toward attractions and destinations in agritourism and associated influential motivation factors. Using data from 413 self-administered questionnaires from six agritourism attractions in Bandung, Indonesia, Partial Least Squares modelling was employed to assess the hypotheses developed. The results reveal the significant impact that experience and satisfaction have on tourist loyalty toward the attraction and agritourism destinations. This study further highlights the indirect effect of both pull and push motivation factors on tourism loyalty toward agritourism attractions and agritourism destinations. Conceptually, this study offers a new understanding of tourist loyalty formation in the growing agritourism context. Managerial implication of these findings is discussed.